(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Poor nutritional awareness and education of mothers have been identified as one of the major causes of child malnutrition in many under developed countries across the world. Malnutrition is a multifaceted problem as it is one of the most significant public health concerns. low nutritional awareness in mothers and household socioeconomic deprivation are the main risk factors of child malnutrition. The mother must be given enough awareness not only regarding the type of food items given to the child but also the knowledge of screening malnutrition and diseases for protection. Patterns of food intake which contribute to accelerated weight gain and overweight. In particular, we focus on describing children’s predispositions and parents’ child feeding practices.